Use of UAVs to assess fire hazard of areas adjacent to trunk pipelines - Sharafutdinov Azat; Abdullin Nail; Balyklov Alexander; Akhmetkhafizov Aydar (E3S Web of Conferences)
The relevance and importance of the problem of environmental monitoring through innovative methods, including the use of unmanned aerial vehicles, is beyond doubt. The purpose of using multi-and hyperspectral complexes based on unmanned aerial vehicles is to increase the efficiency of fire safety control of trunk oil pipelines. The tasks solved by this technology include continuous monitoring of the condition of pipelines with high spatial and temporal resolution, detection and prevention of possible oil or gas leaks, as well as reducing the risks to human life in the process of monitoring the fire safety of oil and gas facilities. The findings confirm that the technology of multi-and hyperspectral complexes based on unmanned aerial vehicles has great potential to improve the safety of the oil and gas industry and reduce the risks of environmental disasters. The results of the analysis of theoretical studies and experimental indicators allow us to conclude about the effectiveness of the use of multi and hyperspectral complexes based on unmanned aerial vehicles in order to continuously monitor the state of oil trunk pipelines, both in terms of optimizing the funds spent and in terms of increasing the efficiency of monitoring.